The climbing Hydrangeas (Hydrangeaceae) of Mexico, including description of six (critically) endangered new species - Samain, Marie-Stéphanie; Hernández Najarro, Francisco; Martínez Salas, Esteban Manuel (Instituto de Ecología, A.C., 2019)
Background and Aims: The genus Hydrangea consists of approximately 200 taxa in Asia and America. Whereas the shrubby species from Asia and the USA, as well as the over 1000 hybrids and cultivars derived from these, are very well known because of their ornamental value, the Neotropical species are much less appreciated. Hydrangea section Cornidia, currently consisting of 13 accepted taxa, occurs from Mexico to Chile and Argentina, with one species in southeast Asia. Its representatives are root-climbing lianas which may grow up to 60 m high in the tree canopy of temperate to (sub)tropical forests. Extensive field work throughout their distribution area and study of herbarium specimens has resulted in the discovery of new taxa. We present here a revision of the ten currently known Mexican species.Methods: Field work was carried out in northwestern, central and southeastern Mexico, including exploration in areas where the genus had not been collected before. Detailed morphological and architectural studies of all species were carried out, based on living plants in their natural habitat, as well as on dried specimens from our own collections and all available herbarium material.Key results: Six Hydrangea species new to science are described here, including an identification key for the native species and one widely cultivated species, illustrations and distribution maps. Additionally, amended descriptions for two earlier described species are presented, as a result of which all currently known native Mexican Hydrangeas now dispose of a detailed morphological description.Conclusions: The genus Hydrangea exemplifies the lack of taxon-specific botanical collection activities in Mexico. The discovery of these new species is even more surprising taking into account the considerable size of these plants. All Mexican Hydrangea species are threatened, mainly due to deforestation and land use changes.